Students’ Interest in Learning English with Teachers who Use Humor in Teaching and Learning Process at SMKN 53 Jakarta - Rinaldi, Ade; Amri, Zul (Journal of English Language Teaching, 2024)
The English learning process was considered difficult and boring for students. This made students lose interest in learning English. Students' interest in learning could emerge through a fun learning process. One way that teachers could use to create a fun learning process was to use humor. In this study, researcher tried to find out students' interest in learning English with teachers who used humor in the teaching and learning process. The population was 12th grade students from SMKN 53 Jakarta while the sample was four classes of 12th grade students at SMKN 53 who were collected using purposive sampling technique. The total participants in this study were 100 students who were collected using questionnaires and strengthened by interviews. This study used a descriptive quantitative method. The data analysis technique used for the questionnaire was the basic method of descriptive statistical analysis while in analyzing interview data researcher used data presentation. Based on the data obtained and analyzed, it was known that students' interest in learning English with teachers who used humor was very high. This could be seen from the average value of 3.352 for feeling pleasure, 3,138 for students’ engagement, 3.2 for students’ attention, and 3.0925 for students’ involvement. The results of the interview data also supported this statement.